A study on epidural analgesia in labour and its foetomaternal outcomes in a tertiary care centre - Surendra Chaudhari, Mihir; John, Susan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Epidural analgesia is considered the most effective method for labour pain relief. However, concerns persist regarding its influence on labour progression, operative delivery and neonatal outcomes. This study evaluated foetomaternal outcomes associated with epidural labour analgesia. Methods: This prospective observational study was conducted over a period of eleven months in a tertiary care teaching hospital. Sample size was calculated using nMaster software with 80% power and 95% confidence, yielding a minimum of 34 participants per group; 50 women were enrolled in each group (total n=100) to enhance power. Parturients were allocated into epidural (n=50) and non-epidural (n=50) groups. Maternal outcomes included pain scores assessed by the Numerical Rating Scale (NRS), duration of labour stages and mode of delivery. Neonatal outcomes included Apgar scores at 1 and 5 minutes and neonatal intensive care unit (NICU) admissions. Statistical analysis was performed using Student’s t-test and Chi-square test, with p<0.05 considered significant. Results: Pain scores were significantly lower in the epidural group at all measured intervals after 15 minutes (p<0.0001). The duration of the first and second stages of labour was significantly prolonged in the epidural group. There was no statistically significant difference in caesarean section rates, instrumental deliveries, Apgar scores or NICU admissions between groups. Maternal complications were minimal and comparable. Conclusions: Epidural labour analgesia provides effective pain relief without increasing caesarean section rates or adversely affecting neonatal outcomes, although it is associated with a modest prolongation of labour.